Improvement of right ventricular function with transcatheter aortic valve implantation. (June 2014) - Ayhan, Hüseyin; Durmaz, Tahir; Keleş, Telat; Sari, Cenk; Aslan, Abdullah Nabi; Kasapkara, Haci Ahmet; Bozkurt, Engin
Abstract Background and aim. It has been demonstrated that right ventricular systolic dysfunction develops soon after surgical aortic valve replacement (s-AVR). While the impact of s-AVR or TAVI on the function of the left ventricle has been studied with various imaging modalities, little is known about the impact on right ventricular function (RVF). In the current study, we evaluated the impact of TAVI on RVF using conventional echocardiography parameters. Methods and results. Echocardiography was performed prior to 24 h, 1 month and 6 months after TAVI. RVF was assessed using (1) tricuspid annular plane systolic excursion (TAPSE); (2) RV Tissue Doppler Imaging (S'); (3) right ventricular systolic pressure (RVSP); (4) Fractional area change (FAC); and (5) RV ejection fraction (RVEF). TAVI was performed through the subclavian artery in two patients and femoral artery in 48 patients with an Edwards Sapien XT valve. TAVI was performed on 50 patients between the dates of December 2012 and June 2013. After TAVI, a statistically significant improvement was observed for all parameters related to RVF (RVSP, RVEF, TAPSE, FAC, RVTDI S'). During the 1st and 6th months this statistically significant improvement continued in TAPSE and FAC, and there was no deterioration in RVSP, RVEF, and RVTDI S during the 1st month but a statistically significant improvement continued in the 6th month. Conclusion. RVF assessed by conventional echocardiography did not deteriorate after TAVI in early and midterm follow-up. Further, TAVI provides improvement of RVF and can safely and efficiently be performed in patients with impaired RVF.